Trend of Climate Change Mitigation Policy Publication In Indonesia: A Systematic Review - Wance, Marno; Herizal, Herizal; Alwi, Alimin; Syahidah, Ummu; Damasinta, Alfiana (Journal of Government Science Studies, 2024)
The study aims to be able to provide a comprehensive view of research and research related to climate change mitigation issues conducted by researchers from Indonesia. The search results found that the publication of articles through the Crossref and Scopus databases were 700 publications of articles on the issue of mitigation and climate change from the period January 2012 to the period December 2022. The results of article selection using the PRISMA method found 140 articles that met the qualifications. The analysis of research findings is divided into the number of studies per year, the type of research, research objectives, the area of science of the article, the distribution of authors, and the number of articles cited and publishers who often publish articles related to climate change mitigation issues during 2012-2022 in Indonesia.